SURVIVAL CURVE ANALYSIS FOR DROSOPHILA MELANOGASTER WITH D-GADD45 OVEREXPRESSION IN THE NERVOUS SYSTEM - E. N. Plyusnina; M. V. Shaposhnikov; E. N. Andreeva; A. A. Moskalev; L. V. Omelyanchuk (Вавиловский журнал генетики и селекции)
Overexpression of the Gadd45 gene in the nervous system of Drosophila melanogaster increases the life span. We have performed the Gompertz approximation of the survival curve and revealed a life span increase as a result of decrease of the R parameter, reflecting the death level at the beginning of adult life, whereas the other Gompertz parameter, α, responsible for final stage of the life, does not change essentially. In addition, we have analyzed the case of radiation hormesis (low doses of radiation increase life span) and found a similar effect. We conclude that it is promising to perform geroprotector screen by testing substances for the ability to decrease R. Its measurement is less labor-consuming than the construction of the complete survival curve.